Computational linguistics and intelligent text processing : 17th International Conference, CICLing 2016, Konya, Turkey, April 3-9, 2016, Revised Selected Papers.: 17th International Conference, CICLing 2016, Konya, Turkey, April 3-9, 2016, Revised Selected Papers. Part II (2018) - Unknown
No abstract available